2003
DOI: 10.1111/j.1349-7006.2003.tb01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of TZT‐1027 (Soblidotin) against vascular endothelial growth factor‐secreting human lung cancer in vivo

Abstract: TZT-1027 (Soblidotin), an antimicrotubule agent, has been demonstrated to show potent antitumor effects, though the relationships among antitumor effect, cytotoxicity and anti-vascular effect of TZT-1027 have not been studied. We established in vivo human lung vascular-rich tumor models using a vascular endothelial growth factor-secreting tumor (SBC-3/VEGF). SBC-3/VEGF tumors exhibited a high degree of angiogenesis in comparison with the mock transfectant (SBC-3/Neo) tumors in a dorsal skinfold chamber model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…TZT-1027 is a novel antitumour agent that inhibits microtubule polymerisation and exhibits potent antitumour activity in preclinical models (Miyazaki et al, 1995;Kobayashi et al, 1997;Natsume et al, 2000Natsume et al, , 2003Natsume et al, , 2006Otani et al, 2000;Watanabe et al, 2000Watanabe et al, , 2006a. We investigated the effect of TZT-1027 on cell cycle progression with the use of tsFT210 cells, which can be synchronised in G 2 phase by incubation at 39.41C and consequent inactivation of Cdc2 (Osada et al, 1997;Tamura et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TZT-1027 is a novel antitumour agent that inhibits microtubule polymerisation and exhibits potent antitumour activity in preclinical models (Miyazaki et al, 1995;Kobayashi et al, 1997;Natsume et al, 2000Natsume et al, , 2003Natsume et al, , 2006Otani et al, 2000;Watanabe et al, 2000Watanabe et al, , 2006a. We investigated the effect of TZT-1027 on cell cycle progression with the use of tsFT210 cells, which can be synchronised in G 2 phase by incubation at 39.41C and consequent inactivation of Cdc2 (Osada et al, 1997;Tamura et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, it inhibits the growth of various human cancer cells at low concentrations . In vivo, TZT-1027 also manifests a broad spectrum of activity against various murine tumours as well as human tumour xenografts, without inducing a pronounced reduction in body weight (Kobayashi et al, 1997;Watanabe et al, 2000Watanabe et al, , 2006aNatsume et al, 2003Natsume et al, , 2006. Furthermore, the drug exhibited a potent antivascular effect on existing vasculature in an advancedstage tumour model (Otani et al, 2000).…”
mentioning
confidence: 99%
“…TZT-1027 showed antitumor activity in vivo against a hypervascular advanced-stage tumor from a VEGFtransfectant lung cancer cell line, whereas VCR and TXT did not. 10 The upregulation of TIMP3 by TZT-1027 is one possible mechanism for the superior antivascular activity of this drug, compared to that of taxanes and Vinca alkaloids.…”
Section: Characterization Of Tzt-1027 In Reference Profilingmentioning
confidence: 99%
“…7,10,15 TZT-1027 also showed potent antitumor activity against a vincristine-resistant cell line. 7 A recent investigation of the mode of action reported that TZT-1027-induced apoptosis and cell arrest in the G 2 /M phase that was independent of caspase-3 or bcl-2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation